2016
DOI: 10.1080/15548627.2016.1147670
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BMI1 induces autophagy-mediated necroptosis

Abstract: The clonal self-renewal property conferred by BMI1 is instrumental in maintenance of not only normal stem cells but also cancer-initiating cells from several different malignancies that represent a major challenge to chemotherapy. Realizing the immense pathological significance, PTC-209, a small molecule inhibitor of BMI1 transcription has recently been described. While targeting BMI1 in various systems significantly decreases clonal growth, the mechanisms differ, are context-dependent, and somewhat unclear. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 61 publications
5
72
0
Order By: Relevance
“…Previous research found that depletion of Bmi‐1 genetically or pharmacologically led to AMPK‐activated autophagy and affected downstream biological behaviors . Our results showed that NaB depleted Bmi‐1 and triggered a marked increase in LC3B‐II, along with a decrease in p62 levels, in both cell lines (Figure E).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Previous research found that depletion of Bmi‐1 genetically or pharmacologically led to AMPK‐activated autophagy and affected downstream biological behaviors . Our results showed that NaB depleted Bmi‐1 and triggered a marked increase in LC3B‐II, along with a decrease in p62 levels, in both cell lines (Figure E).…”
Section: Resultssupporting
confidence: 64%
“…Interestingly, Bmi‐1 has been reported to be an important target of microRNAs that is closely relate to the reversal of EMT processes . In addition, depletion of Bmi‐1 pharmacologically and genetically induces cell death and triggers autophagy in other tumors …”
Section: Introductionmentioning
confidence: 99%
“…The polycomb complex protein BMI‐1 has an essential role in regulating the proliferative activity of leukaemic stem cells and inhibiting its activity could be a potential therapeutic intervention in the clinic 68 . The BMI‐1 inhibitor PTC‐209 induced autophagy and RIPK3 upregulation leading to necroptosis of ovarian cancer cells 69 . Moreover, autophagy induced by chalcone resulted in cIAP1/2 degradation and formation of the ripoptosome that contributed to activate necroptosis to kill cancer cells 70 .…”
Section: Necroptosis For Cancer Therapy?mentioning
confidence: 99%
“…Thus exposure to frontline platinum therapy induces resistance to drugs given in combination such as paclitaxel or as second-line such as doxorubicin. Therefore recently described small molecule inhibitors of BMI1 [24, 29] have the potential to alleviate acquired resistance to chemotherapy when applied in combination with first- or second-line drugs.…”
Section: Introductionmentioning
confidence: 99%